Biological activities and antibacterial biomarker of Sesbania grandiflora bark extract - Pimporn Anantaworasakul (2018)
In the present study, the fractionated extracts of Sesbania grandiflora bark were prepared and evaluated for their biological activities. The ethyl acetate fractionate (EAF) showed high antioxidant activity along with free radical scavenging and reducing mechanisms. The free radical scavenging antioxidant activity of EAF was 69.3 ± 3.6% where its Trolox equivalent antioxidant capacity was 13.6 ± 0.7 mM/mg. EAF exhibited the reducing power equivalent to ferrous sulfate at 152 ± 2 mM/mg and equivalent to gallic acid at 1.05 ± 0.01 mM/mg. In addition, EAF presented high potential on inhibition of bacterial growth with the minimum bactericidal concentration less than 1 mg/mL. Further isolation of EAF using normal-phase open column of silica gel 60, showed that the fractions eluted with the mixture of chloroform and methanol at the ratios of 4:1, 3:2, and 2:3 possessed antibacterial activity. The recovery activity of total different active fractions was 5% EAF, 20 times less than that of EAF. The chromatogram of EAF from a high-performance liquid chromatography was compared with caffeic acid, catechin, coumaric acid, ellagic acid, gallic acid, quercetin, syringin, naringic acid, trans-cinnamic acid, and vanilic acid. The result demonstrated that one major compound of EAF was gallic acid. These results suggest that the fractionated extracts of S. grandiflora bark contained antioxidant and antibacterial activities.